Islamic Bank Performance Improvement Through the Value Added Intellectual Creation Strategy - Supriyadi, Didit (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study is to analyze the performance of Islamic banking through Value Added Intellectual Creation Strategy (VAIC). The sample is 33 banks in the sharia banking industry in Indonesia consisting of 13 sharia commercial banks and 20 Sharia business units in Indonesia. Some variables used as objects in this study include financial risk, value added intellectual creation, and Islamic banking performance. The method used is descriptive and verification with data collected through a questionnaire instrument and interviews with leaders and policy holders in Sharia banks that are sampled. While the data analysis technique used is Partial Least Square. The findings show that Value Added Intellectual Creation is a very important strategy in improving the performance of Islamic banking which is significantly influenced by financial risk and cost efficiency. Nevertheless, there are still other factors that can affect the performance of Islamic banking in Indonesia.